Research on thermal contact resistance between polymer and mold during thin-wall injection molding 薄壁注射成型中聚合物与模具间接触热阻研究 - Jiang, Li; Jiang, Bingyan; Wu, Wangqing; Zhu, Laiyu; Drummer, Dietmar (Zhongnan Daxue Xuebao (Ziran Kexue Ban)/Journal of Central South University (Science and Technology), 2018)
Based on the heat exchange analysis between polymer and mold during thin-wall injection molding, a novel algorithm for calculating thermal contact resistance(RTC) between polymer and mold was proposed. Through combination of experimental and analytical research, the average RTC between polymer and mold during injection molding for a polycarbonate (PC) thin-wall part was obtained, and the influence of the injection molding process parameters and the interface environment between melt and mold on RTC was researched. The results show that RTC between polymer and mold in thin-wall injection molding is not negligible, and it is strongly correlated with the process conditions. RTC decreases with the increase of the melt temperature, mold temperature, dwell pressure and dwell time, and the mold temperature and dwell time have the greatest influence on RTC. Exchanging with higher thermal conductive or higher surface roughness mold core can also reduce RTC.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Interface heat transfer; Process condition; Thermal contact resistance; Thin-wall injection molding